2018
DOI: 10.1093/jscr/rjy307
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumor of the stomach with high-grade sarcomatous dedifferentiation

Abstract: Solitary fibrous tumors (SFT) are uncommon fibroblastic mesenchymal neoplasms that display a wide range of histologic behaviors. These tumors, which are estimated to account for 2% of all soft tissue neoplasms, typically follow a benign clinical course. However, it is estimated that 10–30% of SFTs are malignant and demonstrate aggressive behavior with local recurrence and metastasis up to several years after surgical resection. We report a case of SFT arising from the stomach, which is an exceptionally rare fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The immunophenotype is positive for CD99, CD34, Bcl-2 and vimentin in tumor cells; in addition, focal weak positive expression of CKpan, EMA, SMA, S-100 and desmin is present. ALK, CD68, CD163, CD21, CD23, β-catenin, CD117 and DOG1 are not expressed (26).…”
Section: Discussionmentioning
confidence: 95%
“…The immunophenotype is positive for CD99, CD34, Bcl-2 and vimentin in tumor cells; in addition, focal weak positive expression of CKpan, EMA, SMA, S-100 and desmin is present. ALK, CD68, CD163, CD21, CD23, β-catenin, CD117 and DOG1 are not expressed (26).…”
Section: Discussionmentioning
confidence: 95%
“…Immunophenotypic analysis demonstrated that these tumors were positive for CD34, signal transducer and activator of transcription (STAT)6, CD99, Bcl-2, and vimentin, focally weakly positive for CKpan, epithelial membrane antigen, SMA, S-100, and desmin, and negative for DX2 and villin. 22 , 23 5) Schwannomas are rare in the stomach and occur with a frequency similar to that of gastric leiomyoma. They often occur in the elderly, forming a 2- to 5-cm tumor in the stomach wall.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was found that SFT is localized not only in the intrathoracic organs and structures, but also in extrapleural areas, involving soft tissues and parenchymal organs [13]. SFTs make up <2% of all soft tissue tumors [14,15]. Gastric localization of SFTs is a very rare disease, which by 2018 was published in seven patients, one of whom with pronounced pathohistological dedifferentiation [15].…”
Section: Introductionmentioning
confidence: 99%
“…SFTs make up <2% of all soft tissue tumors [14,15]. Gastric localization of SFTs is a very rare disease, which by 2018 was published in seven patients, one of whom with pronounced pathohistological dedifferentiation [15]. For the first time in the English medical literature, a clinical case with synchronous tumors -rectal achromatic malignant melanoma and gastric solitary fibrous tumor is presented.…”
Section: Introductionmentioning
confidence: 99%